Splenic artery aneurysm rupture in pregnancy: a learning experience - Patel, Nidhi; Barot, Ketul S.; Patel, Jayesh; Patel, Sweety; Sapre, Shilpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Splenic artery aneurysm (SAA) is a rare clinical entity that carries a risk of rupture and life threatening hemorrhage. The objective of this clinical case report is to highlight this rare occurrence during pregnancy to avoid misdiagnosis. A 25 year old primigravida in her 3rd trimester of pregnancy was brought to trauma and emergency care with severe epigastric pain with rapid onset of unexplained shock. The shock was out of proportion to external or visible blood loss or any other injury. She was taken for emergency laparotomy. Intra-operatively, hemoperitoneum was encountered in peritoneal cavity due to ruptured splenic artery aneurysm. Massive transfusion protocol was activated and aneurysmectomy with splenectomy was performed. Post operatively, the patient was transferred to intensive care unit. Unfortunately, the patient succumbed due to complications of irreversible shock. Pregnant women with SAA can present with non-specific symptoms and hypovolemic shock. In such cases of hemorrhage, obstetricians should always keep in mind the other non-obstetric causes of intra-abdominal bleeding.